Ignition temperatures of dust layers and bulk storages in hot environments. (May 2019) - Janès, Agnès; Vignes, Alexis; Dufaud, Olivier
Abstract: In many industrial installations, particulate solids (cereals, agri-food products, coal, plants, etc.) are stored or processed. Self-heating of these products, which can lead to fires and explosions, can occur in a variety of situations. Examples include large storage at room temperature, formation of a layer on a hot surface, layer deposited on a surface – insulating or conductive – in a hot environment or even storage of product exposed to heating on one side. The main parameters that determine the occurrence of self-heating are the size of the container, the temperature, the residence time and the characteristics of the product. Depending on the type of situation encountered and these implementation conditions, the analysis of self-heating risks must be based on specific models and/or parameters. This paper presents the different variants and combinations of the theoretical model from the theory of thermal runaway to represent self-heating, taking into account in particular the symmetry or asymmetry of heating, reagent consumption and boundary conditions. It also discusses their adaptation to the previous identified industrial situations. Nine products were chosen to be representative of those used in the different considered industrial situations. They were subjected to self-heating basket tests in isothermal ovens in order to determine the parameters for applying the described theoretical models. These results were compared with the results of self-heating tests in layers of different thicknesses in a hot environment, on an insulating or conductive plate, using a specially developed test protocol, as well as with the results of standardized tests of minimum ignition temperature in 5 mm layers. This led to the proposal of the most appropriate theoretical model to represent the self-heating phenomenon for each of the four identified industrial situations. This analysis can promote better design of industrial equipment and production conditions (temperatures, volumes or product flows …) in order to prevent fires and explosions. Highlights: Self-heating of divided solid materials can lead to fires and explosions in various industrial situations. Prevention must consider notably material characteristics, volumes and temperatures to design safe production conditions. Specific models from the theory of thermal runaway, corresponding to various industrial situations, are discussed. A new test protocol of self-heating tests in layers in a hot environment on insulating or conductive plate is described. Experimental results of self-heating basket tests, self-heating tests in layers in oven and MIT in 5 mm layers are compared.